1999
DOI: 10.1177/014572179902500105
|View full text |Cite
|
Sign up to set email alerts
|

A Summer Vacation From Diabetes: Evidence From a Clinical Trial

Abstract: Interviews suggested that teenagers need to take a vacation from intensive diabetes care during the summer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 24 publications
0
15
0
2
Order By: Relevance
“…The lack of consistent daily mealtimes and bedtimes for children has been associated with poorer nutrition and academic performance, and more injuries (Flores, Tomany-Korman, and Olson, 2005). Studies have also shown that adherence to routines support the management of children with chronic diseases; those children with Type 1 Diabetes Mellitus had poorer glycemic control during summer vacations when there was a lack of routines, as compared to when school was in session (Boland, Grey, Mezger, and Tamborlane, 1999). …”
Section: Review Of the Literaturementioning
confidence: 99%
“…The lack of consistent daily mealtimes and bedtimes for children has been associated with poorer nutrition and academic performance, and more injuries (Flores, Tomany-Korman, and Olson, 2005). Studies have also shown that adherence to routines support the management of children with chronic diseases; those children with Type 1 Diabetes Mellitus had poorer glycemic control during summer vacations when there was a lack of routines, as compared to when school was in session (Boland, Grey, Mezger, and Tamborlane, 1999). …”
Section: Review Of the Literaturementioning
confidence: 99%
“…The decrease in habitual physical activity, coupled with less programme nutrition intake led to the diminishment of the camp’s positive effects. It had previously been observed that the glycemic control in teens and children generally tend to worsen over the summer holidays 43 . Although the girls had more desirable levels of HbA1c, participants in both the boys and girls groups were unable to maintain any long‐term beneficial effects of the camp.…”
Section: Discussionmentioning
confidence: 90%
“…This is not a surprising result, because good home management of diabetes would be difficult to surpass in the camp setting where, within limits, food intake and activity are at the discretion of the child and insulin doses cannot be individualized for each child's activity and eating. Furthermore, there is evidence that glycemic control in teens using a pump or three or more shots per day tends to worsen slightly over the summer (13).…”
Section: Discussionmentioning
confidence: 99%